2014
DOI: 10.1007/s00330-014-3161-6
|View full text |Cite
|
Sign up to set email alerts
|

MRI-guided percutaneous retrograde drilling of osteochondritis dissecans of the talus: a feasibility study

Abstract: • MRI serves as a useful guidance method for numerous mini-invasive applications. • Retrograde drilling is a cartilage-sparing alternative in the treatment of osteochondritis dissecans. • MRI guidance seems feasible for treatment of osteochondritis dissecans of the talus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…Due to the technical demands of accurate drilling [ 93 ] with a previous study reporting 20 percent failure rate [ 94 ], several techniques has been developed in order to improve the accuracy and decrease operative time. MRI guidance has proved to be helpful in a variety of percutaneous musculoskeletal procedures, and Kerimaa et al demonstrated that MRI guidance has 100 percent accuracy, is safe, and technically feasible with no complications for retrograde drilling of OLTs [ 95 ]. In addition, Hoffmann et al reported that an electromagnetic navigation system (ENS) demonstrated higher accuracy and shorter operative time compared to standard fluoroscopic technique [ 93 ].…”
Section: Surgical Strategiesmentioning
confidence: 99%
“…Due to the technical demands of accurate drilling [ 93 ] with a previous study reporting 20 percent failure rate [ 94 ], several techniques has been developed in order to improve the accuracy and decrease operative time. MRI guidance has proved to be helpful in a variety of percutaneous musculoskeletal procedures, and Kerimaa et al demonstrated that MRI guidance has 100 percent accuracy, is safe, and technically feasible with no complications for retrograde drilling of OLTs [ 95 ]. In addition, Hoffmann et al reported that an electromagnetic navigation system (ENS) demonstrated higher accuracy and shorter operative time compared to standard fluoroscopic technique [ 93 ].…”
Section: Surgical Strategiesmentioning
confidence: 99%
“…The literature concerning RD was mostly constituted by retrospective case series (17 articles, 81%) [ 6 , 8 , 12 – 26 ], classified as LOE IV. The remaining articles were equally divided into retrospective comparative studies (two articles, 10%) [ 7 , 27 ] and prospective observational studies (two articles, 10%) [ 28 , 29 ], both classified as LOE III (Table 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Despite its wide application, current evidence on the indications for and outcomes of RD in the treatment of osteochondral lesions of the ankle is limited, and a comprehensive review is missing. Moreover, in the last few years there has been some evolution of the original technique [ 6 8 ]. Since RD has provided better results compared to anterograde drilling [ 9 ], and the latter is being progressively replaced by microfractures that do not cause heat damage, this review focuses only on RD.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, there are several reports in which retrograde drilling was used for OCD lesions of the knee and ankle, 14 17 and recent studies demonstrated favorable results for retrograde drilling of stable OCD lesions. 18 20 Kono et al 21 also reported that the clinical results of retrograde drilling for OCD of the talar dome were superior to those of antegrade transmalleolar drilling. The advantages of retrograde drilling are that it avoids articular surface violation, 22 and it can be combined with retrograde autologous cancellous bone-grafting if it is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In the reports of OCD lesions of the talus, open MRI scanners and navigation systems tend to be used for the retrograde drilling. 14 , 15 , 18 , 22 , 29 However, for drilling the OCD lesion of the femoral condyle, an image intensifier is often used even now. 20 , 30 32 The reason for this is that it is thought that a clear lateral view of the femoral condyle is more easily obtained compared to the talus, because the femoral condyle is not surrounded by other bones, unlike the talus.…”
Section: Discussionmentioning
confidence: 99%